Innovation in surgical practice: The Association of Surgeons in Training conference - Belfast 2019. (December 2020) - Clements, J.M.; Humm, G.; Nally, D.M.; ,
Abstract: The Association of Surgeons in Training (ASiT) advocates for and represents surgical trainees throughout the United Kingdom and the Republic of Ireland. It promotes excellence in surgical training for the benefit of both surgeons and patients. Originally founded in 1976, ASiT is independent of the National Health Service (NHS), Surgical Royal Colleges, and Specialty Associations. The 2019 Annual Conference in Belfast hosted a record number of delegates (n = 855) over the 3-day educational weekend. The conference theme, "Innovation in Surgical Practice" focused on the latest educational and technological innovation to enhance trainee's knowledge and experience of surgical innovation to ultimately enhance patient care. A record number of technical and non-technical pre-conference courses (n = 13) covering a diverse range of topics was offered. A new feature, a 24-h Hackathon, was successfully delivered in parallel to the Conference. This opportunity generated productive, cross speciality collaboration, to address and solve current problems in healthcare. Over 1000 abstract submissions were received and there were over 30 poster and oral prizes on offer for winning submissions. The ASiT conference and the Association continues to grow annually and we look forward to welcoming delegates to Birmingham from the 6-8th March 2020 to enjoy another action packed weekend focused on "Optimising Performance". Highlights: "Innovation in Surgical Practice" was the theme for the 2019 conference in Belfast. Innovation in Surgery is vital to surgical practice in progressing and enhancing patient care. ASiT hosted the first Surgical 24-hour Hackathon during the conference. The 2020 ASiT International Conference takes place in Birmingham on March 6-8th with the theme "Optimising Performance".